MARKETING SOCIAL - Valero, Paco (La Sociología en sus Escenarios, 2010)
Abstract. Social Marketing has come using to describe, tempting activities destined to increase the acceptability of social causes, ideas or conducts to the individual. The social Marketing is not but that the sales of social ideas, but for that reason do not have less to be despised, since this causes the same effort and steps to arrive at the final mission which is to sell an ideology or way to think certain about a consuming public. Resumen. El Marketing Social se ha venido usando para describir, actividades destinadas a incrementar la aceptabilidad de causas sociales, ideas o conductas apetecibles al individuo.